AB0861 Lectins That Target Sialic Acid Modified Receptors May Hold Therapeutic Potential for Degenerative Arthritis. (9th June 2015) - Mayán, M.D.; Carpintero-Fernandez, P.; Gago-Fuentes, R.; Varela-Eirin, M.; Goldberg, G.S.; Blanco, F.
Abstract : Background: Glycosylated proteins are essential components of the extracellular matrix (ECM) of cartilage and contribute to the maintenance of its function. A shift from a-2, 6- to a-2, 3-linked sialic acids of glycoproteins modifies the binding ability of proteins to substrates influencing cellular anchoring and affecting signal transduction. Intriguingly, the predominance of a-2, 3-sialylation of chondrocytes glycoproteins was associated with the pathophysiology of rheumatic diseases including rheumatoid arthritis (RA) and osteoarthritis (OA). A highly O-glycolysated protein with α-2, 3-sialic acid, involved in the induction of inflammation and tissue repair, is the transmembrane mucin receptor named Podoplanin (PDPN). Objectives: The present study aimed to assess the effect of specifically targets a-2-3-sialic acid residues with a lectin-based drug (MASL) on chodrocyte dedifferentiation and cartilage breakdown processes. Methods: For immunofluorescence and immunohistochemistry assays, in situ cartilage was fixed and frozen immediately using Tissue-Tek O.C.T. and isopentanol in liquid nitrogen. Primary cells in monolayer culture were fixed with formaldehyde for optical microscopy assays. 4mm cartilage punches were prepared from cartilage explants that were cut in the operating room immediately after surgery and cultured in DMEM with 0.1% FCS. Chondrocytes were isolated from articular cartilage and cultured in DMEM with 15% FCS. Cell viability was evaluated by the colorimetric MTT assay. Cell adhesion and grown was assess with fibrinogen-coated well plates and Wound Healing Assay Kit. Reactive oxygen species levels were measured by DCFH-DA and by Flow Cytometry. RNA was isolated with TRIZOL® Reagent and analyzed by Real-Time RT-PCR. Results: The treatment of chondrocytes with 400 and 720 nM of MASL did not affect cell viability, adhesion or growth. To mimic pathological conditions, cells and cartilage explants were treated with 5 μg/ml oligomycin. Treatment of chondrocytes with oligomycin did not affect cell viability but increased ROS levels over 10 fold and MMP3, IL-6 and COX2 mRNA levels over 3-10 folds. The treatment of cells with MASL effectively protected chondrocytes from ROS production when incubated in the presence of oligomycin. Moreover, oligomycin induced the expression of inflammatory cytokines including IL-6 and COX2, and this induction was reverted by treatment with nanomolar concentrations of MASL. 5 μg/ml of oligomycin for 7 days decreased safranin uptake and disrupted the ECM structure of cartilage punches as evidenced by ulceration increasing lacunae space. However, the presence of 400 nM of MASL prevented the cartilage destruction and inhibited COX2 and MMP3 induction by oligomycin treatment. Immunohistochemistry assays revealed that OA cartilage contained significantly higher levels of PDPN protein in comparison with cartilage from healthy donors. Conclusions: This study demonstrates that physiologically relevant concentrations of MASL protect chondrocytes from detrimental effects of ROS, inflammatory cytokines and MMPs and preserve chondrocyte phenotype and articular cartilage structure under pathological conditions. Disclosure of Interest: None declared